New locality of macroalga Ulva prolifera (Ulvaceae) in the Wielkopolska Region - Rybak, Andrzej; Messyasz, Beata (W. SZAFER INSTITUTE OF BOTANY - POLISH ACADEMY OF SCIENCES - KRAKÓW, 2009)
New inland locality of Ulva prolifera O. F. Müller [=Enteromorpha prolifera (O. F. Müller) J. Agardh, Enteromorpha salina Kützing] was found in flowing pond in the Kopla valley, near Tulce country (Wielkopolska Region, locality coordinates: 52o20′35″N; 17o04′40″E). Macroalga thallus had been watched since May till August 2008. U. prolifera thalluses reached significant sizes (above 200 cm long). Thalluses of such sizes have not been described in the literature yet. Macroalga thalluses have been differing greatly in respect of its built in relation to all already known see forms. The pond in which this originally see species lived, was filled with very fertilized water. The eutrophia state present in the U. prolifera locality was caused by the flow of contaminated waters from a production plant nearby the pond, floating to it with Kopla river.
Keywords: freshwater Ulva; Chlorophyta; Enteromorpha prolifera; Enteromorpha salina; Ulva prolifera; Kopla; Freshwater Enteromorpha; Ulvaceae; Wielkopolska Region; Greenalgae; Macroalgae; Tulce